Study of the antibacterial effect of extracts from Lespedecia bicolor and cream based on them - Kiselyova, Kateryna; Osolodchenko, Tatyana; Vyshnevska, Liliia (Annals of Mechnikov's Institute, 2024)
Aim of work. The aim of the work is the microbiological substantiation of the creation of medicinal products with extracts from Lespedeza bicolor for the treatment of infectious and purulent-inflammatory diseases. Materials and methods. The antimicrobial activity of water, alcohol, and oil extraction of the ground part of Lespedecia bicolor, as well as cream with oil and alcohol extraction of Lespedecia compared to the reference drug Calendula ointment was studied. Reference test cultures of microorganisms belonging to different taxonomic groups, as well as clinical isolates, were used for microbiological examination of the samples. The antimicrobial activity of the studied samples was determined by the diffusion method of "wells" and disks with the measurement of the diameters of the growth retardation zones of microorganisms. Results and discussion. It was established that the extraction of the ground part of Lespedeza bicolor has a moderate antimicrobial effect against selected strains of microorganisms. The results showed that relative to the reference strains of microorganisms and clinical isolates, the highest antimicrobial effect is shown by the aqueous extraction of lespedeza. The presence of pronounced sensitivity of test strains of Staphylococcus microorganisms to Lespedeza extractions determined the urgency of developing a cream with oil and alcohol extraction of Lespedeza bicolor. Moderate antimicrobial action of the cream against the test strain S.aureus ATCC 25923 and weak antibacterial action against the test strains Staphylococcus aureus ATCC 6538-Р and Candida albicans ATCC 885-653 and clinical isolates of Staphylococcus aureus 16, Staphylococcus epidermidis 14, Streptococcus pneumoniae 14, Streptococcus pyogenes 2432 and Staphylococcus aureus 124 was experimentally established, which exceeds or is at the level of activity of the reference drug "Calendula ointment". Conclusions. Microbiological studies have established the presence of antibacterial activity of extracts of the Lespedeza bicolor ground part in relation to gram-positive and gram-negative reference strains of microorganisms and clinical isolates. It is shown that the cream with oil and alcohol extraction of Lespedeza in terms of antimicrobial activity exceeds or is at the level of activity of the reference drug "Calendula Ointment".